Complement Dependent and Independent Interaction Between Bovine Conglutinin and Mycobacterium bovis BCG: Implications in Bovine Tuberculosis - Mehmood, Arshad; Kouser, Lubna; Kaur, Anuvinder; Holmskov, Uffe; Al-Ahdal, Mohammed N.; Sim, Robert B.; Kishore, Uday; Tsolaki, Anthony G. (Frontiers in Immunology, 2019)
Bovine conglutinin, the first animal collectin to be discovered, is structurally very similar to Surfactant Protein D (SP-D). SP-D is known to interact with Mycobacterium tuberculosis, and the closely-related M. bovis, the causative agent of bovine tuberculosis. We speculated that due to the overall similarities between conglutinin and SP-D, conglutinin is likely to have a protective influence in bovine tuberculosis. We set out to investigate the role of conglutinin in host-pathogen interactions during mycobacterial infection. We show here that a recombinant truncated form of conglutinin (rfBC) composed of the neck and C-type lectin domains, binds specifically and in a dose-dependent manner to the model organism Mycobacterium bovis BCG. rfBC showed significant direct bacteriostatic effect on the growth of M. bovis BCG in culture. In addition, rfBC inhibited the uptake of M. bovis BCG by THP-1 macrophages (human monocyte lineage cell line) and suppressed the subsequent pro-inflammatory response. Conglutinin is well known as a ligand of the complement activation product, iC3b. rfBC was also able to inhibit the uptake of complement-coated M. bovis BCG by THP-1 macrophages, whilst maintaining the pro-inflammatory response. It is likely that rfBC inhibits the phagocytosis of mycobacteria by two distinct mechanisms: firstly, rfBC interferes with mannose receptor-mediated uptake by masking lipoarabinomannan (LAM) on the mycobacterial surface. Secondly, since conglutinin binds iC3b, it can interfere with complement receptor-mediated uptake via CR3 and CR4, by masking interactions with iC3b deposited on the mycobacterial surface. rfBC was also able to modulate the downstream pro-inflammatory response in THP-1 cells, which is important for mobilizing the adaptive immune response facilitating containment of mycobacterial infection. In conclusion, we show that conglutinin possesses complement-dependent and complement-independent anti-mycobacterial activities, interfering with both the known major mechanisms of mycobacterial uptake by macrophages. As mycobacteria are specialized intracellular pathogens, conglutinin may inhibit M. bovis and M. tuberculosis from establishing an intracellular niche within macrophages, and thus, negatively affect the long-term survival of the pathogen in the host.